WHO Guidelines for the Management of Postpartum Haemorrhage and Retained Placenta. - Organization, World Health (Nonserial Publications., 2009)
Effective treatment of postpartum haemorrhage (PPH) often requires simultaneous multidisciplinary interventions. The health care provider needs to begin resuscitative efforts quickly, establish the cause of the haemorrhage, and possibly obtain the assistance of other care providers, such as an obstetrician, anaesthetist or radiologist. Avoiding delays in diagnosis and treatment will have significant impact on sequelae and chance of survival. These guidelines therefore include care pathways for the management of PPH, as a practical guide for clinicians. A loose-leaf insert of these care pathways.